Percepção de estudantes sobre aspectos didático-pedagógicos e tutoria em módulo temático saúde da criança de curso de especialização a distância - GARCIA, Renato Barros (2017)
This is an analytical observational study, with a quantitative and qualitative approach, conducted in the Child Health Module 1 of a Postgraduate Distance Learning Course. The goals of this study were: to analyze a general evaluation of the students about the module and tutoring; To test diferences around the conduction of the tutor in the evaluated activities; To verifying the distribution of the students' evaluation about didactic-pedagogical aspects and tutoring; To identify the items referring to pedagogical didactic aspects and tutoring that had the most influence in the overall evaluation of the module; And to evaluate the comments of the students on the categories of the qualitative analysis. The sample comprised 774 students from a total of 2189 students enrolled in the classes evaluated. About the overall evaluation of the module, 61% of the students rated it as optimal, and only 1% as bad / insufficient. Regarding tutoring, 70.4% of the students evaluated as optimal in the module, and only 0.4% as bad / insufficient. There was no significant difference in the comparative analysis of the frequencies of the tutor's performance in the forum or posting activity (p = 0.718). There was also no statistically significant difference in the qualification of the type of book offered in the module (p = 0.941). Regarding the evaluative activity, the questionnaire presented the best classification (56% optimal concept, 40.4% good). In the qualification of the module planning variables, the best evaluated item was the importance of this for professional practice (70.5% optimal, 28.6% good). There were significant differences between the variables of the platform aspects (p = 0.042), the item that stood out was "adequacy of educational resources" obtaining 60.1% of optimal evaluations, 37.7% of good. Within the criteria of students' evaluation about tutoring, the item that stood out was "encouraging participation, dialogue and exchange of experience among course participants," regarded as optimal by 70.5% of the course participants; Good, by 28.3% and as bad / insufficient by only 1.2%. In the multiple linear model, four variables did not present significant influence on the general concept of the module: Online book (P = 0.134), Post Activity (p = 0.158), Hourly load (p = 0.191), and Access and functionality (P = 0.191). Revealing that the great majority of didactic aspects offered, had positive determination in the overall evaluation of the module by the students. In relation to the tutoring, it was found that all variables were determined in the general concept of the tutor, to quote: Domain the contents of the module; The theory and practice integration in the mediation of knowledge; It values the previous knowledge of the students, relating them to the content of the module; Encourage participation, dialogue and exchange of experience among the students; Gives Feedback on activities highlighting coherent points, points that can be improved or new points of view. It was observed that in both evaluation activities the tutor's performance was considered positive, demonstrating that he had an adequate posture in teaching and learning through them. It was verified the relevance in the tutor's work mainly in the creation of a pleasant environment and favorable to this exchange of experiences and dialogue favors the debate of relevant topics and awakens interest, thus facilitating the exchange of ideas and construction of knowledge. Future research may add other factors in understanding students' assessment of module and mentoring.